Correlation between Pod Shape Traits and Its Fiber Quality of Wild Calotropis Gigantea - Yumei Cui; Longdi Cheng; Xiaohong Shan; Wenhong Fan (Journal of Natural Fibers, 2017)
Seed fiber in the Calotropis gigantea (C. gigantea) pods is the most valuable component and can be developed into textile material. Cultivating high-yield and high-quality seed fibers for C. gigantea is one of the critical preconditions for its textile industrialization. In this paper, pods picked from wild C. gigantea plants were used as the experimental materials. The fiber length distribution of the pods was studied. The pod characters (pod shape, single pod weight, fiber weight per pod and seed number per pod, etc.) and the crucial quality characteristics of seed fibers (length, diameter and strength) were tested. The correlations between them were analyzed. The results show that the fiber lengths at the tip, the petiole and the middle part of the pods are significantly different: the fibers from the two sides of the middle part are the longest and more uniform. The pod shape is closely correlated with the fiber length, fineness and strength: longer pods have longer fiber length, smaller length variation and larger fiber diameter, and the percentage of low strength fiber (single fiber strength <1.2 cN) is significantly lower compared to smaller pods. Cultivating C. gigantea with large size and heavy pods will improve the seed fiber yield and the fiber quality.